Hidden and uninterested populations: Methodological insights and unresolved issues from the study of Cannabis Social Clubs. Issue 3 (November 2020) - Pardal, Mafalda; Bone, Melissa; Decorte, Tom; Queirolo, Rosario; Parés, Òscar; Johansson, Julia; Álvarez, Eliana; Repetto, Lorena
Cannabis Social Clubs are typically non-profit associations established by adult users of cannabis, which produce and distribute cannabis among their members. Such associations can be found in several European countries and beyond, but with exception of Uruguay, they are illegal or otherwise operate at the margins of domestic drug control legislation, at risk for law enforcement detection. We have conducted several individual and collaborative studies on Cannabis Social Clubs and their key actors (e.g. Cannabis Social Clubs leaders, users affiliated as members, cannabis growers, other stakeholders), primarily drawing on qualitative methods (e.g. ethnographic fieldwork, interviews, qualitative media analyses) but also employing a quantitative approach (e.g. online surveys). In this article, we reflect on the research experiences of the authors in studying Cannabis Social Clubs, providing insights for future research in this area and within criminology and socio-legal studies. In particular, we aim to examine our approaches with regard to the recruitment of participants and research design, identifying good practices, but also discussing what the less successful strategies were. We draw on research conducted since 2014 in different countries, with different legal frameworks, which provides an opportunity for a comparative and more in-depth critical consideration of what might be helpful ways of reaching and researching hard-to-reach populations.